Antecedents on organizational citizenship behavior and its impact on organizational commitment in nurses in Tk. II Moh Ridwan Meuraksa Hospital Jakarta in 2023 - Wijaya, Kinaryochi; Oscar Jayanegara; Victorio, Victorio (Enrichment : Journal of Management, 2024)
RS. TK. II Moh. Ridwan Meuraksa Hospital is a Class B Military Hospital owned by the TNI AD (Indonesian Army) located at Jl. Raya Taman Mini 1 Pinang Ranti, East Jakarta. According to the Ministry of Health data, there are currently around 1.5 million healthcare workers and 150,000 medical staff in Indonesia. Nurses constitute the largest group, with a ratio of 2 per 1,000 population. The aim of this study is to determine the influence of job satisfaction, workplace spirituality, and organizational commitment on organizational citizenship behavior and its impact on work productivity among nurses at RS. TK. II Moh Ridwan Meuraksa Jakarta. This research adopts a quantitative approach, specifically a cross-sectional study design. Hypothesis testing in this study employs certain inferential statistical methods. The measurement is conducted using a Likert scale with five points: 1 (Strongly Disagree), 2 (Disagree), 3 (Neutral), 4 (Agree), and 5 (Strongly Agree). The results of the study indicate a significant positive influence among the variables of job satisfaction, workplace spirituality, and organizational commitment on organizational citizenship behavior and work productivity, as evidenced by p-values < 0.05 and t-statistic > 1.985.